Democracia e participação social no Conselho Municipal do Meio Ambiente e Desenvolvimento Sustentável (CADES), da cidade de São Paulo – SP/Brasil - Fugimoto, Carolina Ramos (2022)
Democracy and Social Participatory in Municipal Management Council of Environment and Sustainable Development (CADES), the present dissertation deals with how the Democracy, in Brazil, since Brazilian Federal Republic Constitution was proclaimed, in 1988, with Municipal autonomy enlarge in the Federation mode (articles 1º and 18 of Federal Constitution); the law nº. 6938/81 reception´s (Nacional Environmental Policy), cities growth, the social participatory increase in conflicts resolution, gave chance to arise the Municipal Management Council, in the cooperative Federative structure at sharing environment´s issues, special at São Paulo City. The São Paulo City Hall, through Municipal Green and Environment Office (SVMA) – as local institution of the Nacional System of Environment (SISNAMA) – is responsible of City environment management and carries out relevant function to foment discuss in the Environmental Agenda, in the Communities pursue goals, management and administer your conflicts, realize environmental governance in an open space, transparent, respecting the individual and the public, in the course of a Smart City, more and more fair and better life conditions for people, in line as Besties Smarts Cities in the World, for São Paulo City Hall context…Is this the present study purpose. Based on current legislation and actualized, bibliography research and literary review, taking account personal experience at sundries departments in Municipal Green and Environment Office, especially in CADES. As conclusion, hope as with this analysis verify progress and retreats into this relevant Municipal Management Council with Environmental Agenda, with Sustainable Development Goals and Democratic System, permitting new purposes for a more Participatory Democracy and more balanced popular participatory at CADES, and, maybe, without this pretension, inspire another cities search law and sustainable cities ways.